The Role of Brand Image in Mediating the Effect of Electronic Word of Mouth (E-WOM) and Social Media on Purchase Intention - Dede Solihin; Ahyani Ahyani (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aimed to investigate the function of brand image in mediating the impact of social media and electronic word-of-mouth on purchase intention. Methods The causality technique is employed in this study. Customers who purchase on South Tangerang's Lazada marketplace make up the study's demographic. Purposive sampling was employed to select samples from up to 150 respondents. SEM (Structural Equation Model) analysis with the SMART PLS program was employed for the data analysis. The research showed that social media and electronic word-of-mouth (E-WOM) had a favorable and significant impact on brand perception. Brand image can act as a mediator between Electronic Word of Mouth (E-WOM) and social media factors on purchase intention. E-WOM and social media have a favorable and significant impact on purchase intention. The findings of this study suggest that social media and electronic word-of-mouth (E-WOM) can, directly and indirectly, improve purchase intention through brand image.